Research Methodology in Food Sciences: Integrated Theory and Practice, 1st edition - C. O., Mohan (Apple Academic Press, 2020)
Here is a rich resource on recent research innovations in the field of food processing and food engineering. Chapters are written by eminent researchers in the field of food science and provide in-depth knowledge on the application of engineering aspects in food processing, food packaging, food quality, and food safety.